1996
DOI: 10.1074/jbc.271.47.29854
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stearoyl-CoA Desaturase 1 mRNA Stability by Polyunsaturated Fatty Acids in 3T3-L1 Adipocytes

Abstract: The effects of arachidonic acid (20:4, n-6) and other fatty acids on the expression of stearoyl-CoA desaturase gene 1 were investigated in fully differentiated 3T3-L1 adipocytes. Treatment of 3T3-L1 adipocytes with arachidonic acid resulted in a decrease in stearoyl-CoA desaturase (Scd) enzyme activity and scd1 mRNA. Arachidonic acid did not alter the transcription of the scd1 gene, whereas the half-life of the scd1 mRNA was reduced from 25.1 to 8.5 h. Blocking the conversion of arachidonic acid to eicosanoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
93
3
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 44 publications
15
93
3
3
Order By: Relevance
“…One possible explanation can be found in the increase in PUFA content in liver as BT was reduced in feeds. It has been reported that PUFA inhibit the activity of stearoyl-CoA-desaturase, the enzyme that synthesizes oleic acid from stearic acid, thus regulating its expression (Sessler et al, 1996). This inhibition could lead to accumulation of the precursor (C18:0), and reduction in MUFA content, which might also be affected by the lower MUFA supply in the diet as vegetable fat increased in feeds.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation can be found in the increase in PUFA content in liver as BT was reduced in feeds. It has been reported that PUFA inhibit the activity of stearoyl-CoA-desaturase, the enzyme that synthesizes oleic acid from stearic acid, thus regulating its expression (Sessler et al, 1996). This inhibition could lead to accumulation of the precursor (C18:0), and reduction in MUFA content, which might also be affected by the lower MUFA supply in the diet as vegetable fat increased in feeds.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy might be explained by the fact that PUFA contents of the experimental rations used by Archibeque et al (2005) were not constant thereby interfering with proper interpretation of the data. Indeed, PUFA are known to have a down-regulating effect on the activity of SCD (Sessler et al, 1996;Ntambi, 1999;Velliquette et al, 2009). In beef cattle, it was specifically shown that the SCD activity in muscle and adipose tissue was lower on a diet rich in n-3 PUFA compared with n-6 PUFA (Herdmann et al, 2010;Hiller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PUFA have a down-regulating effect on the activity of SCD (Ntambi, 1999). Both n-3 and n-6 PUFA may depress SCD activity as shown in vitro in hepatocytes (Velliquette et al, 2009) and adipocytes (Sessler et al, 1996). In beef cattle, SCD gene expression in muscle and SCD protein expression and enzyme activity in muscle and adipose tissue was significantly lower on a diet rich in n-3 PUFA compared with n-6 PUFA (Herdmann et al, 2010;Hiller et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The mechanism of PUFA-mediated repression of lipogenic gene expression in adipocytes is different from that described in liver. PUFA also decrease SCD1 mRNA levels in 3T3-L1 adipocytes (Sessler et al 1996). PUFA suppress the expression of the SCD1 gene in adipocytes by decreasing mRNA stability.…”
Section: Effect Of Polyunsaturated Fatty Acids On Adipose Tissue Genementioning
confidence: 99%
“…In order to further address the molecular basis by which PUFA might influence adipose tissue gene expression, it has been shown that PUFA act directly on adipocyte gene expression (Grimaldi et al 1992;Amri et al 1994;Sessler et al 1996;Mater et al 1998). This finding indicates that PUFA-mediated regulation of adipose tissue gene expression would not necessarily need extra-adipose factors.…”
Section: Effect Of Polyunsaturated Fatty Acids On Adipose Tissue Genementioning
confidence: 99%